Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1021/jp003041q
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Spectra of Several Metal Complexes Revisited by the Time-Dependent Density-Functional Theory-Response Theory Formalism

Abstract: Vertical excitations calculated for the , , RuO4, CrF6, FeCp2, RuCp2 and CpNiNO species are compared to experimental spectra. The results obtained from the time-dependent density-functional theory−response theory (TD-DFRT) method are compared to both previously reported ΔSCF calculations and experiment. The results show that, in general, excited states of metal oxide and metallocene compounds are well described by TD-DFRT. However, serious difficulties are met with the CrF6 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 49 publications
4
76
0
Order By: Relevance
“…6,10,12,15 Excited state number 2 at 2.24 eV seems to be responsible for the shoulder at 2.35 eV, which was suggested by Scott and Becker 16 and by Scuppa et al 12 to arise from a triplet excitation. The assignment of excited state 2 to the 2.35 eV shoulder, however, is in agreement with the disappearance of this peak and the color change of ferrocene from orange to yellow upon cooling.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 80%
See 2 more Smart Citations
“…6,10,12,15 Excited state number 2 at 2.24 eV seems to be responsible for the shoulder at 2.35 eV, which was suggested by Scott and Becker 16 and by Scuppa et al 12 to arise from a triplet excitation. The assignment of excited state 2 to the 2.35 eV shoulder, however, is in agreement with the disappearance of this peak and the color change of ferrocene from orange to yellow upon cooling.…”
Section: Journal Of Chemical Theory and Computationmentioning
confidence: 80%
“…It is demonstrated that B3LYP works perfectly fine and that the differences between B3LYP results and experiment found in earlier studies arise from incorrect assignment of the excited states, 6,10,12,15 use of inadequate pseudopotentials, 6 and that agreement between theory and experiment at other levels of theory was manipulated by using Cp−Fe distances that were too short. 6,12 Based on ligand field theory, the low-energy peaks are assigned to be d−d transitions and the stronger absorptions to charge-transfer (CT) states. 15,21 Analysis of density differences and charge differences on Fe between ground and excited states reveals that low-and high-lying excited states involve similar amounts of charge transfer, so that the distinction between n d−d and CT transitions 21 is not justified.…”
Section: ■ Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As an illustrative example we computed the lowlying singlet excitation spectrum of ferrocene for which experimental solution data [61,62] as well as ample theoretical ab initio gas-phase reference values [49,50,[63][64][65] are available.…”
Section: Ferrocenementioning
confidence: 99%
“…[44,45] As the calculations on excitedstate properties using post-Hartree-Fock methods require more computational effort, time-dependent density functional theory (TD-DFT) would be attractive in the present study due to its lower computational cost and more superior results than single-excitation configuration interaction (CIS) or time-dependent Hartree-Fock (TD-HF) in predicting the vertical electronic excitation spectra. [46][47][48] …”
Section: A C H T U N G T R E N N U N G [Nds*a C H T U N G T R E N N Umentioning
confidence: 99%